The Experiment Practical Design of Marine Auxiliary Engine Monitoring and Control System - Ruddianto, Ruddianto; Nugraha, Anggara Trisna; Pambudi, Dwi Sasmita Aji (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2021)
Maintaining the quality of transportation services and reducing operational costs are some of the problems in shipping companies. This problem can be solved by several solutions. One of them is a reliable machine alarm monitoring and operation system. This study aims to provide a practical design of the ship's auxiliary engine start-stop control system and alarm system. This study uses an experimental method with a descriptive explanation of the observations. The test results show that this system is able to provide a simple, inexpensive, and efficient engine alarm system design to develop this technology for shipping companies. The PLC used is suitable for controlling this system because of its fast response. In addition, the utilized HMI can communicate efficiently with the monitoring system showing the machine parameter interface directly. Direct application of the system has been created provides technology development solutions for monitoring and controlling systems auxiliary machines for shipping companies to reduce operational cost.